Current Predictors of Mortality in Veteran Patients Undergoing Major Lower Extremity Amputations: Risk Factors Have Not Changed and Mortality Remains High. Issue 5 (May 2023) - Tsai, Shirling; Lanier, Heather D.; Tran, Nguyen; Pham, Thai; Huerta, Sergio
Major lower extremity amputation (LEA—above the ankle) carries a high rate of mortality. In the present study, we performed an institutional review of all patients submitting to LEAs at a Veteran Administration Hospital (between 2009 and 2021) accompanied with a review of the literature. For the past 12 years, 1042 LEAs were performed in 603 patients at our hospital. The 30-day, 1-year, and 5-year mortalities were 8.5%, 28.9%, and 53.0%, respectively. Age, hypoalbuminemia, and Clavien-Dindo Class were independent predictors of mortality in all the time intervals in the analysis. Cardiac disease was not an independent predictor of mortality. In 39 studies reviewed, the average 30-day, 1-year, and 5-year mortality was 14%, 36%, and 56%, respectively. There was no difference in mortality in multiple studies analyzed. No significant temporal variation was identified between 1950 and 2000 vs. 2001 and 2021. Predictors of mortality were not substantially different from our institutional experience. The mortality rate for LEAs remains constant over time. Increasing age and hypoalbuminemia are strong predictors of short- and long-term mortality.